Rare genetic variants affecting platelet count: Results from a genome-wide association study - Jóhann Hauksson 1992- (2019)
Platelets are anuclear blood cells formed in the bone marrow. In the bloodstream, their primary functions are involvement in hemostasis and immunity. Abnormal platelet count (PLT) is a potential indication of pathological disequilibrium in thrombopoiesis or platelet survival, which can lead to thrombosis or excessive bleeding. Furthermore, epidemiological studies have associated altered PLT with mortality, cardiovascular disease and malignancies. Various factors determine PLT, although genetic factors are thought to be of major importance. In recent years, extremely rare causative genetic variants have been discovered in family studies of inherited platelet disorders. Genome-wide association studies (GWAS) have also identified multiple genetic variants associatied with PLT. However, there is still lack of studies that systematically assess contribution of rare variants with large effects in determination of various traits, including PLT. The purpose of this study is to search for rare genetic variants that affect platelet count and observe their frequencies in other populations. Materials and methods The data used in this study consist of 32,637,387 genetic variants identified through whole-genome sequencing of 28,075 individuals and imputation into 155,250 chip-typed individuals (direct imputation) as well as their 285,664 untyped 1st and 2nd degree relatives (familial imputation). Collectively, 440,914 individuals are included in the study cohort. PLT measurements were extracted from three of the largest clinical laboratories in Iceland: i) Landspítali University Hospital of Iceland (LSH), (ii) Akureyri Regional Hospital and (iii) Icelandic Medical Center Laboratory in Mjódd. Data processing was conducted using software developed at deCODE genetics. Results and discussion 14 novel variants were identified in this study. All of them have a minor allele frequency (MAF) under 1% and are associated with large effects on PLT. The variants are dispersed over 11 loci, of which 10 have previously been implicated in ...